Analisis Kesalahan Penggunaan Ejaan Bahasa Indonesia dalam Surat Resmi Organisasi Mahasiswa (Ormawa) Politeknik Negeri Jember - Lely Dian Utami; Milawaty; Riski Kuara (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
The aim of this research is to analyze errors in the use of Indonesian spelling in official documents issued by student organizations (Ormawa) at Politeknik Negeri Jember. This research was conducted by considering that in writing official organizational letters, errors are often encountered especially in using correct Indonesian spelling, including in official letters written by the student organizations at Politeknik Negeri Jember. These organizations include UKM (Student Activity Unit), HMJ (Department Student Association), MPM (Student Consultative Council), BEM (Student Executive Body), and IMP (Study Program Student Association). The research methods used were literature study and documentation by collecting 16 official letters from 16 student organizations at Politeknik Negeri Jember. Data analysis was carried out by using descriptive-qualitative method, guided by the 2022 Enhanced Spelling (EYD) Edition V. The results of the analysis showed that there were errors in the use of Indonesian spelling in the official letter issued by the student organizations at Politeknik Negeri Jember. These errors include: 1) errors in the use of letters, including the use of italics, capital letters and bold letters; 2) errors in the use of words, including errors in writing abbreviations and derivative words; and 3) errors in the use of punctuation, including errors in the use of apostrophes ('), colons (:), commas (,), and hyphens (-). It is hoped that this research can serve as a guide and joint evaluation in writing official organizational letters, as well as providing benefits for campus organizations in particular and the public in general.